Exploring the Connection Between Hyperuricemia and Cardiovascular Disease in Patients with Ischemic Heart Disease - Nabibullaeva Shodiyaxon Z; Makxmudova Muniraxon S; Nuritdinova Nigora B; Shukurdjanova Surayyo M (Zien Journals, 2024)
This study explores the relationship between hyperuricemia and various cardiovascular risk factors in patients diagnosed with ischemic heart disease (IHD). A comparison was made between two groups: patients with hyperuricemia and IHD (Group 1) and a control group without IHD (Group 2). Results indicate significant differences in thale volume, blood pressure, cholesterol, triglycerides, and lipoprotein levels, suggesting that hyperuricemia may exacerbate cardiovascular risks. These findings underscore the need for routine monitoring and management of uric acid levels in at-risk populations.
Keywords: monitoring; acid; significant; volume